Analysis of Acceptance of Three Variants of Jemblem Cake Based on Hedonic Test and Organoleptic Test - Ali Shodiqin, Muhammad; Nur Qomariyah, Umi Kulsum (AGARICUS: Advances Agriculture Science & Farming, 2024)
Processed food has become a product that is very popular. Cassava is an agricultural commodity that is widely grown in Indonesia and is an important source of carbohydrates after rice. This research aims to evaluate the quality of organoleptic tests and hedonic tests of jemblem as a product that is high in carbohydrates. By using organoleptic tests such as taste tests, distinctive aroma tests, sweetness, and impressions evaluated by trained panelists. The results show that jemblem has a savory and sweet taste, has a typical vanilla aroma, and a sweet taste from red sugar and has an overall positive value. Next, the hedonic test is a general liking test in terms of taste, distinctive aroma, sweetness. The three tests were calculated using anova with a calculated F of 0.131. Findings showed a high level of acceptance, with most respondents expressing high levels of satisfaction and interest in consuming this product as a substitute for rice. With the high carbohydrate potential of jemblem, this product can be considered as a healthy and delicious food alternative, opening up opportunities for further development in the traditional food industry